A Comprehensive Review of Avascular Necrosis (AVN) Treatment Modalities in Orthopedics - Mateńko, Jan; Możarowski, Wiktor; Pietruszka, Wiktoria; Klasicki, Przemysław; Mozer, Maciej; Pałuchowski, Michał; Krupa, Agata; Kiełbratowska, Julia; Potrykus, Maria; Krawczyk, Anna (Quality in Sport, 2025)
Avascular necrosis (AVN), also known as osteonecrosis, aseptic necrosis, or ischemic bone necrosis, describes a pathological condition characterized by bone tissue death due to disrupted blood supply, leading to bone death and potential joint collapse. This review aims to provide an overview of the current treatment strategies for AVN, encompassing both conservative and surgical interventions. Emphasis is placed on recent advancements, including biological therapies and novel surgical techniques, to guide orthopedic practitioners in evidence-based decision-making.